1995
DOI: 10.1523/jneurosci.15-11-07565.1995
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic axons pathfind successfully in the absence of target

Abstract: To determine whether sympathetic axons require the presence of a peripheral target to grow to the correct destination, we examined the developing footpad innervation in tabby mutant mice which lack sweat glands. Despite the absence of sweat glands, noradrenergic sympathetic axons are transiently present in the presumptive target area and avoid the more distal epidermal/dermal domain occupied by sensory axons. Since sympathetic axon pathfinding was not dependent upon the target tissue, we compared the subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 55 publications
3
33
0
Order By: Relevance
“…Sympathetic axons pathfind successfully in the absence of their target tissues (Guidry and Landis, 1995). Fig.…”
Section: Cell Migrationmentioning
confidence: 99%
“…Sympathetic axons pathfind successfully in the absence of their target tissues (Guidry and Landis, 1995). Fig.…”
Section: Cell Migrationmentioning
confidence: 99%
“…(H) GPA (2 ng/ml), CNTF (1.5 ng/ml), CLC/CLF (100 ng/ml) and NP (500 ng/ml) induce the expression of VIP in cultures of chick sympathetic neurons. Whereas detectable stores of endogenous catecholamines disappear in neurons innervating sweat glands in rats and mice, THand DBH-IR were reported to decrease to low levels in rats but to be maintained in mice (Rao et al, 1994;Guidry and Landis, 1995). The lack of catecholamine production in mouse sweat gland innervation was explained by a loss of the TH cofactor tetrahydrobiopterin and the tetrahydrobiopterin synthetic enzyme GTP cyclohydrolase (GCH) (Habecker et al, 2002).…”
Section: Quantitative Analysis Of Tuj1-ir Is Shown In (C) (D-f) Sweamentioning
confidence: 99%
“…Because of signals derived from this target, adrenergic traits such as catecholamine production are downregulated, whereas the induction of cholinergic features, like choline acetyl transferase (ChAT), vesicular acetylcholine transporter (VAChT) and the co-expressed neuropeptide vasoactive intestinal peptide (VIP), leads to a functionally cholinergic sweat gland innervation. The importance of the target tissue for this transmitter phenotype switch to occur has been firmly established by sweat gland transplantation, by replacement by parotid gland (Schotzinger and Landis, 1990) and by analysis of the tabby mouse mutant, which is devoid of sweat glands (Guidry and Landis, 1995). Cholinergic sympathetic neurons innervate, as additional target tissues, the skeletal muscle vasculature and the periosteum, the connective tissue covering the bone.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that substantial TH immunoreactivity is still present in sweat glands of adult mice; however, catecholamine histofluorescence that is present at P4 largely disappears by P21 in mice (Guidry and Landis, 1995). Thus although levels of TH remain high in mice, catecholamine synthesis is switched off as cholinergic synthesis is switched on, similar to that observed in rats (Landis and Keefe, 1983).…”
Section: Discussionmentioning
confidence: 55%
“…Our work in the mouse, however, demonstrates a gradual increase in the expression of both TH and VIP between P7 and P21, although the glands are functionally cholinergic. Guidry and Landis (1995) demonstrated that TH-immunoreactive fibers innervate the developing sweat glands as early as P4, and the number of THpositive fibers increases dramatically by P14. Rao et al (1994) Figure 5.…”
Section: Discussionmentioning
confidence: 98%